2009
DOI: 10.1111/j.1365-2966.2009.15892.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the star formation history of elliptical galaxies: beyond simple stellar populations with a new line strength estimator

Abstract: We study the stellar populations of a sample of 14 elliptical galaxies in the Virgo cluster. Using spectra with high signal‐to‐noise ratio (S/N ≳ 100 Å−1) we propose an alternative approach to the standard side‐band method to measure equivalent widths (EWs). Our boosted median continuum is shown to map the EWs more robustly than the side‐band method, minimizing the effect from neighbouring absorption lines and reducing the uncertainty at a given S/N. Our newly defined line strengths are more successful at dise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…In fact, Rogers et al (2010) have shown that the mixture of two SSPs is the most reliable approach to describe the stellar population of early-type galaxies. Most recently, Lopez-Corredoira et al (2017) fit a set of 20 red galaxies with models of a single-burst SSP, combinations of two SSPs as well as an extended star formation history.…”
Section: Stellar Population Parametersmentioning
confidence: 99%
“…In fact, Rogers et al (2010) have shown that the mixture of two SSPs is the most reliable approach to describe the stellar population of early-type galaxies. Most recently, Lopez-Corredoira et al (2017) fit a set of 20 red galaxies with models of a single-burst SSP, combinations of two SSPs as well as an extended star formation history.…”
Section: Stellar Population Parametersmentioning
confidence: 99%
“…It also has the advantage of reducing the uncertainty in the total flux of our measured spectral bands (Rogers et al 2010). The BMC method is sensitive to two parameters and a balancing act must be played with both.…”
Section: Effect Of Pseudo-continuum Placementmentioning
confidence: 99%
“…The BMC method is based on two parameters: (1) the width of the window around a given wavelength and (2) the percentile of the flux which defines the pseudo-continuum. We started by assuming the parameters used in Rogers et al (2010), a window of 100 Å with a percentile of 90 per cent. The effect of the choice of these parameters is analyzed in detail in Section 3.7.…”
Section: Processing Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Also note there that in NGC 4278 obsIDs 7081 was taken prior to obsID 7080, and we therefore retain the chronological sequence with obsID 7081 labeled as pointing 5 in subsequent figures. Age estimates are from (a) Terlevich & Forbes (2002), (b) Kuntschner et al (2010), and (c) Rogers et al (2010). et al (2001).…”
Section: Notesmentioning
confidence: 99%